From Single Screen to YouTube: Tracking the Regional Blockbuster. (December 2018) - Srinivas, S. V.; Shyam, V. H. C. V. Megha; Nanduri, Raghav; Singhal, Vasundhara; Vishnu Dath R.
Recent developments related to production, distribution and viewing of movies point to the need for research projects that examine multiples sites and formats simultaneously. This article outlines an ongoing project whose primary objective is to track the migration of movies across geographical spaces as well as screens. Our starting point—the pretext rather—is the 'regional blockbuster' that is the name we have given to big budget productions made by Chennai- and Hyderabad-based film industries. The regional blockbuster, being an all-India form that circulates in multiple language versions, offers opportunities for comparisons across regions in India and also between theatrical and other spaces of movie consumption. In the current phase, the focus of our project is the transformation of single screen cinema halls on the one hand and dubbing on the other. These, we suggest are among the necessary conditions for the emergence of the blockbuster. We present here the initial findings of fieldwork carried out by us simultaneously in Kerala, Andhra Pradesh, Telangana and Delhi.